Metrica e biografia nel primo Fortini - De Luca, Bernardo (L'ospite ingrato, 2025)
The article examines the early Fortini by relating his metrical choices to his intellectual formation. The analysis of the Foglio di via princeps shows that the collection is not only a prelude to his mature work but also preserves formal possibilities later abandoned. The opposition between elegy and wartime rhythms reveals a poetics in balance, where metre registers inner tensions. Macrotextual connections outline a cohesive path intertwining themes and forms, showing how Fortini moves beyond the model of “song” to shape a more self-aware and problematising mode of expression.